Великие православные праздники - Глаголева Ольга (Православные святыни, 2001)
Экземпляры: ф.6 (20161026) / Инвентарный номер: 1928 / Цена: / Сис.шифр: 86.372 / Авт.знак: В 27 / ГРНТИ: 21.15.61 / ББК: 86.372